The Contestation of the Narratives of "Change" versus "Sustainability" on the Instagram Accounts of Two 2024 Presidential Candidates - Suryawati, Indah; Ikhwan, Muhammad; Siregar, Rachmi Kurnia (Nyimak: Journal of Communication, 2025)
The implementation of the 2024 Presidential Election cannot be separated from the dynamics of the use of social media as a medium for political communication, and Instagram is one of the social media used to convey political messages to the public. In this study, these political messages are manifested in the form of political narratives that compete with each other on social media. This research aims to (1) analyze the framing of the political narratives of Anies Baswedan and Prabowo Subianto uploaded on their Instagram accounts; and (2) how the ideas behind these political narratives are articulated. A qualitative approach was used in this study and Entman's framing analysis model was used as the method. The research findings reveal a fundamental conflict within the political narratives of Anies Baswedan and Prabowo Subianto. This contestation of political narratives is geared toward strengthening electability and capturing public attention. Prabowo's concept of sustainability demonstrates his desire to continue pro-people programs deemed successful during Jokowi's administration (Jokowinomics), such as various assistance programs for the underprivileged. Unlike Prabowo Subianto, Anies Baswedan emphasized ideas for change, such as eradicating poverty in Indonesia. The final results of the 2024 presidential election demonstrated that the political narrative regarding the need for sustainability successfully led Prabowo to victory.Keywords: 2024 Presidential Election, Instagram, framing, political narrative, Anies Baswedan, Prabowo Subianto ABSTRAKPelaksanaan Pilpres 2024 tidak dapat terlepas dari dinamika penggunaan media sosial sebagai media komunikasi politik, dan Instagram menjadi salah media sosial yang dimanfaatkan untuk menyampaikan pesan-pesan politik kepada khalayak. Dalam penelitian ini, pesan-pesan politik tersebut mewujud dalam bentuk narasi politik yang kemudian saling berkontestasi satu sama lain di media sosial. Penelitian ini bertujuan (1) menganalisis pembingkaian narasi politik Anies Baswedan dan Prabowo Subianto yang diunggah di akun Instagram keduanya; (2) bagaimana artikulasi ide-ide yang ada di balik narasi politik tersebut. Studi ini menggunakan pendekatan kualitatif serta model analisis framing Entman sebagai metode. Hasil penelitian menunjukkan adanya pertentangan fundamental dalam bingkai narasi politik Anies Baswedan dan Prabowo Subianto. Kontestasi tersebut mengarah pada upaya memperkuat elektabilitas serta merebut perhatian publik. Ide keberlanjutan yang diusung Prabowo menunjukkan keinginan Prabowo melanjutkan program-program pro rakyat yang dinilai berhasil pada era pemerintahan Jokowi (Jokowinomics), misalnya berbagai program bantuan untuk masyarakat pra sejahtera. Berbeda dari Prabowo, Anies Baswedan lebih menonjolkan ide-ide perubahan, misalnya memberantas kemiskinan di Indonesia. Hasil akhir Pilpres 2024 kemudian menunjukkan bahwa narasi politik mengenai perlunya keberlanjutan berhasil mengantarkan Prabowo menuju kemenangan.Kata Kunci: Pilpres 2024, Instagram, framing, narasi politik, Anies Baswedan, Prabowo Subianto